Activity of Kersen (Muntingia calabura L.) and Kasturi (Mangifera casturi Kosterm.) Extract as Afrodisiac - Karunita Ika Astuti; Aristha N. Putri; Revita Saputri; Ika P. Sari; Teuku N.S. Sulaiman (Indonesian Journal of Pharmaceutical Science and Technology, 2023)
Kasturi (Mangifera casturi Kosterm.) is a typical plant of South Kalimantan, and Kersen (Muntingiacalabura L) contains flavonoids and steroids was empirically used for aphrodisiac. However, nopreclinical trials using that extracts. This research to test the aphrodisiac activity to optimal dose isobtained and the possibility of a synergistic or toxic effect if the two extracts are combined. Thestudy aimed to determine of secondary metabolites and the aphrodisiac effect of extracts. The testused a completely randomized design into 8 groups. Parameters measured were frequency approach(introduction), riding (climbing), and mating (coitus). The results showed the Kasturi have of flavonoid,Steroid, and Phenol. Kersen extract have contained saponins, phenol, flavonoid, steroid. Kersen extract200 mg/kg BW dose shows the highest rather than the others. The combination of kersen and kasturiextracts of 100 mg/kgBW and 200 mg/kg BW doses did not show better effect when compared to asingle dose. It can be concluded that the aphrodisiac activity in the combination of kersen and kasturiextracts tends not synergis.